Síntese, caracterização e aplicação do MCM-41 e A1-MCM-41 na pirólise do resíduo atmosférico de petróleo - Castro, Kesia Kelly Vieira de (2009)
In present work, mesoporous materials of the M41S family were synthesized, which were discovered in the early 90s by researchers from Mobil Oil Corporation, thus allowing new perspectives in the field of catalysis. One of the most important members of this family is the MCM-41, which has a hexagonal array of mesopores with pore diameters ranging from 2 to 10 nm and a high surface area, enabling it to become very promising for the use as a catalyst in the refining of oil in the catalytic cracking process, since the mesopores facilitate the access of large hydrocarbon molecules, thereby increasing the production of light products, that are in high demand in the market. The addition of aluminum in the structure of MCM-41 increases the acidity of the material, making it more beneficial for application in the petrochemical industry. The mesoporous materials MCM-41 and Al-MCM-41 (ratio Si / Al = 50) were synthesized through the hydrothermal method, starting with silica gel, NaOH and distilled water. CTMABr was used as template, for structural guiding. In Al-MCM-41 the same reactants were used, with the adding of pseudoboehmite (as a source of aluminum) in the synthesis gel. The syntheses were carried out over a period of four days with a daily adjustment of pH. The optimum conditions of calcination for the removal of the organic template (CTMABr) were discovered through TG / DTG and also through analysis by XRD, FTIR and Nitrogen Adsorption. It was found that both the method of hydrothermal synthesis and calcination conditions of the studies based on TG were promising for the production of mesoporous materials with a high degree of hexagonal array. The acidic properties of the materials were determined by desorption of n-butylamine via thermogravimetry. One proved that the addition of aluminum in the structure of MCM-41 promoted an increase in the acidity of the catalyst. To check the catalytic activity of these materials, a sample of Atmospheric Residue (RAT) that is derived from atmospheric distillation of oil from the Pole of Guamaré- RN was used. This sample was previously characterized by various techniques such as Thermogravimetry, FTIR and XRF, where through thermal analysis of a comparative study between the thermal degradation of the RAT, the RAT pyrolysis + MCM-41 and RAT + Al- MCM-41. It was found that the Al-MCM-41 was most satisfactory in the promotion of a catalytic effect on the pyrolysis of the RAT, as the cracking of heavy products in the waste occurred at temperatures lower than those observed for the pyrolysis with MCM-41, and thereby also decreasing the energy of activation for the process and increasing the rates of conversion of residue into lighter products